2009
DOI: 10.1002/ijc.24581
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thyroid cancer in survivors of childhood cancer: Results from the British Childhood Cancer Survivor Study

Abstract: Second primary neoplasms (SPNs) are a recognised late effect of treatment for childhood cancer. Thyroid SPNs can develop after exposure to low-dose radiation, due to the radio-sensitivity of the thyroid gland. The British Childhood Cancer Survivor Study (BCCSS) was set up to directly monitor the late effects of treatment, including risk of SPNs, in childhood cancer survivors and includes 17,980 5-year survivors. We carried out a cohort analysis to determine the risk of thyroid SPNs in the BCCSS, and estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
3
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 23 publications
4
61
3
5
Order By: Relevance
“…This subtype is the most frequent one, not only in the general population, but also following treatment for childhood malignancy. 11,13,37,38,40,41 Some authors found that being less than 10 years of age was associated with an increased risk of thyroid cancer, 11,13,38 although we did not find similar results. In contrast, we confirmed that women are at an increased risk of developing thyroid cancer (HR=4.74; P=0.002), which has been suggested by other studies 13 and observed in the general population.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This subtype is the most frequent one, not only in the general population, but also following treatment for childhood malignancy. 11,13,37,38,40,41 Some authors found that being less than 10 years of age was associated with an increased risk of thyroid cancer, 11,13,38 although we did not find similar results. In contrast, we confirmed that women are at an increased risk of developing thyroid cancer (HR=4.74; P=0.002), which has been suggested by other studies 13 and observed in the general population.…”
Section: Discussioncontrasting
confidence: 96%
“…36 Many previous studies have focused on thyroid cancer after treatment for childhood cancer. 13,30,[37][38][39] The reported prevalences varied, which may be due to several factors, e.g., the studies were frequently retrospective, based on questionnaires, or included small numbers of patients. In contrast, our study was prospective and included a large number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cancers observed are papillary carcinoma and its follicular variants, with no observed systemic metastasis and the probability of developing metastatic disease is small in these patients. Exposure to low-dose ionizing irradiation of the head and neck has been shown to be associated with an increase in the incidence of thyroid nodules and carcinoma during childhood (11,13,16). However, the level of excess risk remains unclear, as not all the population systematically underwent ultrasound screening and some were not screened at all.…”
Section: Discussionmentioning
confidence: 99%
“…The nodules were bilateral in eight (38%) of the 21 patients. Nodule diameter ranged from 6 to 40 mm, with a median value of 13.7 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) mm.…”
Section: Ultrasound Findingsmentioning
confidence: 99%
See 1 more Smart Citation